Lyubertsy Study of mortality in patients with acute myocardial infarction (LIS): the analysis of anamnestic predictors of in-hospital mortality - S. Yu. Martsevich; M. L. Ginsburg; N. P. Kutishenko; A. D. Deev; A. V. Fokina; E. V. Daniels (Кардиоваскулярная терапия и профилактика)
Aim. To identify the main anamnestic predictors of mortality in the acute phase of acute myocardial infarction (AMI). Material and methods. The study included all patients admitted to Lyubertsy District hospitals and diagnosed with AMI (n=1133). Results. Out of 1133 hospitalised patients, 172 died in the hospital; in-hospital lethality was 15,2%. Mean age of diseased patients was significantly higher than that in those survived. The risk of in-hospital death was significantly and independently associated with older age (relative risk 1,07). After adjustment for age and sex, other independent predictors of in-hospital AMI death included diabetes mellitus (DM), low physical activity, and selected psychosocial factors. Conclusion. The in-hospital lethality levels, observed in the LIS Study, were typical for the Russian Federation. The main anamnestic predictors of in-hospital death were low physical activity, DM, and psychosocial risk factors.